Konstruksi Hukum Keluarga di Indonesia melalui Pendekatan Psikologi - Jon Iskandar Bahari (Universitas Al-Hikmah Indonesia, 2018)
This paper wants to look at the study of psychology in the construction of family law in Indonesia and to know the reconstruction of family law development in Indonesia with a psychological approach. This is motivated by the lack of family law studies using a psychological approach and is an ef ort to contribute to the development of family law from various perspectives, especially with a psychological approach. This research includes library research that uses several sources related to research problems. The results of this study indicate that the development of family law in Indonesia is indeed still less than a concern with a psychological approach. The construction of family law development in Indonesia through a psychological approach can at least be related to three things, namely about family education, emotional maturity, and handling partner violence.